A 40‐year climatology of summer heavy hourly rainfall over mountainous Shanxi in China. (24th August 2021) - Dong, Chunqing; Zhang, Da‐Lin
Abstract: In this study, a statistical analysis of the spatiotemporal characteristics of summer heavy hourly rainfall (HHR) events during 1979–2018 over mountainous Shanxi Province is performed in order to examine regional climate change over such a transition region between North China and Northwest China. Results show that the regional 40‐year annual mean summer rainfall is about 272 mm, about 37% of which is associated with HHR events. High‐frequency and high‐intensity HHR events tend to take place in eastern mountainous subregions, whereas most basin subregions experience HHR events with low frequency and low intensity, showing the important influences of local topography and its interaction with prevailing large‐scale flows. The important topographical influences are also reflected by the observations that most mountainous subregions exhibit a major late‐afternoon peak with a secondary early morning maximum, and that the associated diurnal variations are much greater in amplitude than those in basin subregions. It is found that the regional total annual summer rainfall has a decreasing trend during the first 20 years, mostly by non‐HHR contributions, but a rapid increasing trend during the recent 20 years, with dominant HHR contributions. Most subregions with the increasing trends of HHR frequency are those dominated by rapidly increasing surface temperatures. In particular, more frequent HHR events occur over major urbanization areas, that are in close proximity to complex topography, during the recent two decades. The decadal trends in HHR are found to be correlated to the distribution and intensity changes of the East Asian summer monsoon. The above results have important implications to the operational prediction of HHR events, and a better understanding of regional climate change over mountainous Shanxi Province. Abstract : Summer rainfall over Shanxi Province exhibits a decreasing trend during 1979–1998, mostly by none heavy hourly rainfall (HHR) contributions, but a rapid increasing trend during 1999–2018, with dominant HHR contributions. Most subregions with the increasing HHR trends are those dominated by rapidly increasing surface temperatures, especially over major urbanization areas. High‐frequency and high‐intensity HHR events take place in eastern mountainous subregions, whereas most basin subregions experience HHR events with low frequency and low intensity, showing the important influences of local topography.